장기요양서비스 수급 후기노인의 인지향상 프로그램 중재 효과 - 이홍자; 이도현; Lee, Hung Sa; Lee, Dohyun (지역사회간호학회지, 2013)
Purpose: This study was conducted to test effects of a cognition activation program on ADL, cognitive functions, depression, and QOL in the institutionalized elderly. Methods: The subjects were 40 elders who were admitted to a nursing home, with 20 of them in the experimental group and the other 20 in the control group. Data were collected from September 1 to December 17, 2012. The experimental group participated in a 12 week intervention program. ADL, cognitive functions, depression, and QOL were measured before and after the intervention. Data were analyzed by t-test and regression analysis of the SPSS and AMOS programs. Results: ADL (t=2.468, p=.017), depression (t=-2.625, p=012), and QOL (t=2.428, p=.020) were more significantly improved in the experimental group than in the control group, but there were no statistical differences in cognitive function between the two groups. Cognitive functions had positive effects on ADL (CR=-2.263, p=.024) and depression affected QOL (CR=-7.248, p<.001). Conclusion: The intervention program had positive effects on ADL, depression, and QOL except cognition. Cognitive functions of elders dramatically decrease after age 85, and it takes too much time to improve it. Therefore the program for the improvement of cognitive functions should be provided as early as possible.